Picking winners: Managerial ability and capital allocation - Andreas Benz; Peter R. Demerjian; Daniel Hoang; Martin E. Ruckes (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2024)
We examine how division managers' human capital affects internal capital allocation using a hand-collected data set of divisional managers at S&P 1,500 firms. Based on a novel measure of division-manager ability, we show that more able division managers receive substantially larger capital allocations. This effect is robust to controlling for the possibility of assortative matching and more pronounced for firms with better governance. We also find that the allocation of extra capital to higher-ability managers creates firm value. These findings suggest efficient fund transfers to high-productivity managers and provide support for a largely unexplored bright side of internal capital markets.
Keywords: G31; G32; G34; J24; 330; Managerial Ability; Managerial Efficiency; Human Capital; Capital Budgeting; Investment; Internal Capital Markets